Efficacy and Safety of Quarter-Dose Blood Pressure–Lowering Agents: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 1 (July 2017) - Bennett, Alexander; Chow, Clara K.; Chou, Michael; Dehbi, Hakim-Moulay; Webster, Ruth; Salam, Abdul; Patel, Anushka; Neal, Bruce; Peiris, David; Thakkar, Jay; Chalmers, John; Nelson, Mark; et al.
Abstract : There is a critical need for blood pressure–lowering strategies that have greater efficacy and minimal side effects. Low-dose combinations hold promise in this regard, but there are few data on very-low-dose therapy. We, therefore, conducted a systematic review and meta-analysis of randomized controlled trials with at least one quarter-dose and one placebo and standard-dose monotherapy arm. A search was conducted of Medline, Embase, Cochrane Registry, Food and Drug Administration, and European Medicinal Agency websites. Data on blood pressure and adverse events were pooled using a fixed-effect model, and bias was assessed using Cochrane risk of bias. The review included 42 trials involving 20 284 participants. Thirty-six comparisons evaluated quarter-dose with placebo and indicated a blood pressure reduction of −4.7/−2.4 mm Hg ( P <0.001). Six comparisons were of dual quarter-dose therapy versus placebo, observing a −6.7/ −4.4 mm Hg ( P <0.001) blood pressure reduction. There were no trials of triple quarter-dose combination versus placebo, but one quadruple quarter-dose study observed a blood pressure reduction of −22.4/−13.1 mm Hg versus placebo ( P <0.001). Compared with standard-dose monotherapy, the blood pressure differences achieved by single (37 comparisons), dual (7 comparisons), and quadruple (1 trial) quarter-dose combinations were +3.7/+2.6 ( P <0.001), +1.3/−0.3 (NS), and −13.1/−7.9 ( P <0.001) mm Hg, respectively. In terms of adverse events, single and dual quarter-dose therapy was not significantly different from placebo and had significantly fewer adverse events compared with standard-dose monotherapy. Quarter-dose combinations could provide improvements in efficacy and tolerability of blood pressure–lowering therapy. Abstract : Supplemental Digital Content is available in the text.